A patient-specific planning target volume used in 'plan of the day' adaptation for interfractional motion mitigation - Chen, Wenjing; Gemmel, Alexander; Rietzel, Eike (Journal of radiation research, 2013)
We propose a patient-specific planning target volume (PTV) to deal with interfractional variations, and test its feasibility in a retrospective treatment-planning study. Instead of using one planning image only, multiple scans are taken on different days. The target and organs at risk (OARs) are delineated on each images. The proposed PTV is generated from a union of those target contours on the planning images, excluding voxels of the OARs, and is denoted the PTV 'GP-OAR' (global prostate-organs at risk). The study is performed using 'plan of the day' adaptive workflow, which selects a daily plan from a library of plans based on a similarity comparison between the daily scan and planning images. The daily plans optimized for GP-OAR volumes are compared with those optimized for PTVs generated from a single prostate contour (PTV SP). Four CT serials of prostate cancer patient datasets are included in the test, and in total 28 fractions are simulated. The results show that the daily chosen GP-OAR plans provide excellent target coverage, with V95 values of the prostate mostly > 95%. In addition, dose delivered to the OARs as calculated from applying daily chosen GP-OAR plans is slightly increased but comparable to that calculated from applying daily SP plans. In general, the PTV GP-OARs are able to cover possible target variations while keeping dose delivered to the OARs at a similar level to that of the PTV SPs.
Gesehen am 09.04.2021